SEJARAH PENUBUHAN INSTITUSI FATWA DI NEGERI SELANGOR - Abdul Wahab, Mazni (Jurnal Syariah, 2019)
The administration of fatwa in Selangor that has started well before Merdeka, has undergone phenomenal change. Specific legal provisions have largely underscored various aspects of the administration of fatwa including the appointment and authority of Mufti, the establishment of Syariah Consultative Committee and the organisation of the administration of fatwa.